2010
DOI: 10.1111/j.1742-7843.2010.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

(‐)‐Epigallocatechin Gallate Inhibits Endothelin‐1‐Induced C‐Reactive Protein Production in Vascular Smooth Muscle Cells

Abstract: Abstract:Numerous studies have shown that C-reactive protein (CRP), a pro-inflammation cytokine, makes a direct contribution to atherosclerosis, and that (-)-epigallocatechin gallate (EGCG) is able to exert an anti-atherosclerotic effect by antioxidative and anti-inflammatory activities. Based on our previous study, the effect of EGCG on endothelin-1 (ET-1)-induced CRP production in rat vascular smooth muscle cells (VSMCs) and the possible mechanism were observed. The in vitro experiments showed that EGCG conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This is consistent with a positive association (not significant) seen between CO and VEGF, in this work (Additional file 1 : Table S1). Meanwhile, in this work UFP is associated with increased plasma endothelin (ET-1) (Table 7 ) and increasing trend (not significant) in CRP (Additional file 1 : Table S1), and ET-1 is known to induce CRP via MAPK signaling in vascular smooth muscle cells and effect vasopressor responses [ 77 ]. These results are consistent with the positive associations seen between UFP and heart rate, as well as CRP and heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a positive association (not significant) seen between CO and VEGF, in this work (Additional file 1 : Table S1). Meanwhile, in this work UFP is associated with increased plasma endothelin (ET-1) (Table 7 ) and increasing trend (not significant) in CRP (Additional file 1 : Table S1), and ET-1 is known to induce CRP via MAPK signaling in vascular smooth muscle cells and effect vasopressor responses [ 77 ]. These results are consistent with the positive associations seen between UFP and heart rate, as well as CRP and heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…EGCG has been shown to attenuate oxidative stress in human VSMCs via activation of heme oxygenase-1 39 . In addition, EGCG can relieve oxidative stress by inhibiting endothelin-1-stimulated generation of C-reactive protein in VSMCs 40 . In the present study, we demonstrated that EGCG strongly protected against H 2 O 2 -induced VSMCs apoptosis via activation of caspase family and Bcl-2 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…EGCG decreased the risk of cardiovascular disease by reducing inflammatory markers in rats fed an atherogenic diet [26]. EGCG inhibited endothelin-1-stimulated generation of C-reactive protein in vascular smooth muscle cells, which relieved the inflammatory response and oxidative stress by blocking ROS signals and producing an antiatherosclerotic effect [27]. EGCG inhibited cytosolic subunits of NADPH oxidase from translocating into membrane suggesting inhibition of NADPH oxidase activity in cutaneous mastocytoma cells [28].…”
Section: Discussionmentioning
confidence: 99%